Epidemiological Study of the Brucellosis in Iran, Isfahan, 2010-2015 - Alireza Salahshouri; Javad Ramezanpour; Hamid Gheibipour (Shahrekord University of Medical Sciences, 2021)
Background and aims: Brucellosis is one of the most common infectious diseases in both humans and animals. It has been controlled in developed countries; however, it is still regarded as a public health problem in developing countries including Iran. The aim of this study was to investigate the epidemiology of human brucellosis in Isfahan province. Methods: The present study is a cross-sectional descriptive study investigating the epidemiology of human brucellosis in Isfahan province from 2010 to 2015. Sampling was done using Isfahan's disease registry database. Chi-square and t test were used for analyzing the data, and all data analyses were performed using SPSS software version 21.0. Results: A total of 3,245 patients were included in this study, and their mean (SD) age was 35.29 (18.00) years. The age group of 15-25 years with a frequency of 23.80% had the highest frequency of the disease. The annual incidence of the disease from 2010 to 2014 shows an increasing trend, reaching from 6.25 to 15 per 100 000 people. It was reduced in 2015 and reached 12.25 per 100 000. In addition, the highest incidence was observed in July. Conclusion: This study implies that the trend of human brucellosis has been increasing over the years, so it is recommended that people be educated on how to prevent it in humans and animals. The results of this study can help health administrators in the province to more effectively control the disease at the provincial level by identifying high-risk cities and focusing on health care in these areas.